A randomised placebo controlled trial of pegylated interferon α in active ulcerative colitis. Issue 12 (21st November 2003) - Tilg, H; Vogelsang, H; Ludwiczek, O; Lochs, H; Kaser, A; Colombel, J-F; Ulmer, H; Rutgeerts, P; Krüger, S; Cortot, A; D'Haens, G; Harrer, M; et al.
Abstract : Background: Pilot studies of interferon α (IFN-α) suggest a high remission rate in the treatment of active ulcerative colitis. We evaluated the safety of pegylated interferon α (PegIFN) and its role in induction of remission in patients with active ulcerative colitis, in a multicentre placebo controlled trial. Methods: Sixty patients with a clinical activity score (CAI) of >6 were randomised to receive placebo (n = 20), PegIFN 0.5 μg/kg (n = 19), or PegIFN 1.0 μg/kg body weight (n = 21) once weekly (PegIntron; Schering-Plough, USA) over 12 weeks. Patients receiving 5-aminosalicylates, steroids, and/or azathioprine in stable dosages were included. Results: Serious adverse events were seen in none of the placebo patients, in 3/19 patients in the PegIFN 0.5 μg/kg group (hospitalisation due to disease flare up n = 3), and in 3/21 in the PegIFN 1.0 μg/kg group (hospitalisation due to disease flare up n = 1; thrombosis n = 1; grand mal seizure n = 1). Otherwise, we observed only minor IFN-α side effects. Clinical remission rates at week 12 (CAI ⩽4) were 7/20 (35%) in the placebo, 9/19 (47%) in the PegIFN 0.5 μg/kg group, and 7/21 (33%) in the PegIFN 1.0 μg/kg group (NS). Early withdrawal from the study was observed in 11/20 placebo patients, in 6/19 in the PegIFN 0.5 μg/kg group, and in 10/21 in the PegIFN 1.0 μg/kg group, mainly due to lack of efficacy. The higher PegIFN dose was associated with a significant decrease in levels of C reactive protein (p = 0.003, day 0 v 85). Conclusions: PegIFN is safe but not effective, at the dosages used, in patients with ulcerative colitis.